PORTFOLIO OPTIMIZATION USING MARKOWITZ METHOD FOR CRYPTOCURRENCY, INDONESIA STOCK MARKET, AND GOLD (2014–2024) - Zaidaan Rizq Vinsa Putra; Subiakto Sukarno (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
This research focuses on portfolio optimization by leveraging Markowitz Modern Portfolio Theory (MPT) along with Sharpe ratio to analyze the inclusion of Bitcoin in diversified investment portfolios along with the LQ45 Index and gold. The methodology begins with collecting historical data of the underlying asset and the risk-free rate during the period from October 2014 to October 2024, followed by calculating the expected returns, standard deviations, and covariances. This research compares two different portfolio scenarios, with and without Bitcoin. The results shows that portfolio that incorporate Bitcoin have higher return and have better risk-adjusted performance compared to portfolio without Bitcoin during this period. This highlighted the potential for Bitcoin to contribute for enhancing portfolio performance and yielding better return with a given level of risk, providing valuable insight for portfolio diversification and underscore Bitcoin as a high-risk and high-return asset in modern financial markets.